Bioactive Potential of 3D-Printed Oleo-Gum-Resin Disks: B. papyrifera, C. myrrha, and S. benzoin Loading Nanooxides—TiO2, P25, Cu2O, and MoO3 - Diogo José Horst; Sergio Mazurek Tebcherani; Evaldo Toniolo Kubaski; Rogério de Almeida Vieira (Bioinorganic Chemistry and Applications)
This experimental study investigates the bioactive potential of filaments produced via hot melt extrusion (HME) and intended for fused deposition modeling (FDM) 3D printing purposes. The oleo-gum-resins from benzoin, myrrha, and olibanum in pure state and also charged with 10% of metal oxide nanoparticles, TiO2, P25, Cu2O, and MoO3, were characterized by ultraviolet-visible (UV-Vis) and Fourier transform infrared (FTIR) spectroscopy, energy-dispersive X-ray microanalysis (EDXMA), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). Disks were 3D-printed into model geometries (10 × 5 mm) and the disk-diffusion methodology was used for the evaluation of antimicrobial and antifungal activity of materials in study against the clinical isolates: Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. Due to their intrinsic properties, disks containing resins in pure state mostly prevent surface-associated growth; meanwhile, disks loaded with 10% oxides prevent planktonic growth of microorganisms in the susceptibility assay. The microscopy analysis showed that part of nanoparticles was encapsulated by the biopolymeric matrix of resins, in most cases remaining disorderly dispersed over the surface of resins. Thermal analysis shows that plant resins have peculiar characteristics, with a thermal behavior similar to commercial available semicrystalline polymers, although their structure consists of a mix of organic compounds.